TUMEFACTIVE MULTIPLE SCLEROSIS: A DIAGNOSTIC ENIGMA. A CASE REPORT - Magdalina Yanakieva; Maya Danovska; Emilia Ovcharova; Diana Marinova; Nicholas Shepherd (Peytchinski Publishing, 2023)
Purpose: To present a clinical case of tumefactive multiple sclerosis (TMS), which is an inflammatory demyelinating disease of the central nervous system considered to be a rare form of multiple sclerosis (MS). It belongs to the group of borderline forms of MS - a collective term used to define a spectrum of demyelination-associated neurological conditions that share similar clinical, neuroimaging and histopathological features but vary widely in severity, clinical course and outcome. Materials/Methods: We describe the case of a 31-year-old female who was admitted to the Neurology clinic of UMHAT "Dr Georgi Stranski" in Pleven, Bulgaria, with a rapid onset of neurological deficit including right-sided hemiparesis, dysarthria, imbalance, cognitive impairment and urinary incontinence. MRI of the brain showed several tumor-like concentric lesions of demyelination surrounded by moderate brain edema, consistent with the radiological criteria for the demyelinating disease. Results: High-dosage corticosteroids were applied intravenously for this patient as acute therapy. A progressive improvement in the patient was achieved after the extended pulse corticosteroid therapy in combination with physiotherapy. Glatiramer acetate as a disease-modifying treatment was initiated within three months and had substantial efficacy. Conclusions: The diagnosis of TMS is always difficult and requires not only complex clinical and neuroimaging investigations but also an extensive follow-up of the patient. It is believed that TMS usually has a progressive course and an unfavorable outcome, but a relapsing-remitting course of TMS, albeit rare, is also possible. Our case report confirms that such benign variants of TMS exist. We believe that highlighting such complex clinical cases will contribute to a better understanding of the mystery of MS.